Hubungan Pengetahuan Gizi, Asupan Lemak dan Perilaku Merokok dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Kondodewata Kabupaten Tana Toraja - Esrianti Sambu; Irmawati Irmawati; Jalil Genisa (Lembaga Pengembangan Kinerja Dosen, 2024)
Hypertension is a condition when the systolic blood pressure in the human body is ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Hypertension is dangerous because it has an impact on cardiovascular disease. The aim of this research is to determine the relationship between nutritional knowledge, fat intake and smoking behavior with the incidence of hypertension in the community in the Kondodewata Community Health Center working area.The type of research used was quantitative with a cross sectional design. The population in this study was 238 people aged >15 years with a research sample of 75 people using a simple random sampling technique. The instruments used were questionnaires for nutritional knowledge and smoking behavior, while the Food Recall for Fat Intake was then processed in the form of univariate analysis and bivariate analysis with p value = 0.05.The results of this study show that there is a relationship between nutritional knowledge and the incidence of hypertension in the Kondodewata health center working area with p value = 0.014. There is a relationship between fat intake and the incidence of hypertension in the Kondodewata health center working area with p value = 0.000. There is no relationship between smoking behavior and the incidence of hypertension in the Kondodewata health center working area with p value = 0.072.The conclusion of this study shows that nutritional knowledge and fat intake are related to the incidence of hypertension in the Kondodewata health center working area. Meanwhile, smoking behavior has no relationship with the incidence of hypertension in the Kondodewata Community Health Center working area. It is recommended that health workers in the Kondodewata health center work area provide education to the public regarding nutritional knowledge, fat consumption patterns and the dangers of smoking.